The Effectiveness of a Meta Cognitive Strategy on Developing the Scientific Reasoning, Self Efficacy & Decision Making Skill in Science Teaching among Student-Teachers - Yahya M. Abu Jahjouh (Sultan Qaboos University, 2014)
The current research aimed at investigating the effectiveness of a meta cognitive strategy on developing scientific reasoning, self efficacy and decision making skills in teaching science among science studentteachers. Science teaching strategies course 2 prescribed for science majors at Al-Aqsa University was selected for experimentation. The researcher selected two sections: one as experimental (n= 48) and the other as control group (n= 53). The researcher designed three instruments: a 24- multiple choice questions of scientific reasoning test; a 48- item self-efficacy in science teaching scale, and a 30-questions decisionmaking in science teaching test. The validity of the scientific reasoning test was ensured via referees' validity and its reliability through split-half method (0.87) Reliability was ensured via computing alpha Cronbach (0.82) and split half method (0.90) The decision-making test was 0.81. Before the start of the experiment, the three instruments were administered to the groups, and the means, standard deviations, ttest for two independent samples were computed. The findings showed that: there were statistically significant differences (p < 0.01) in favor of the experimental group in self-efficacy and decision making, whereas no statistically significant differences were observed in scientific reasoning. The researcher recommended using the meta cognitive strategy in University instruction and decreasing verbal teaching strategies.